The Impact Of Knowledge Sharing And Innovation On Performance: The Mediation Role Of Innovation - Utama Melisha Hidayat; Yulia Hendri Yeni; Vera Pujani (Institute of Computer Science (IOCS), 2022)
Management research maintains organizational performance during the Covid-19 pandemic by requiring it to act effectively and efficiently in managing the business based on relevant knowledge. Efforts are needed to support the organization by maintaining the key to success based on knowledge sharing and innovation in improving business performance, therefore the organization can survive during the crisis. This study aims to investigate the mediating role of innovation on the relationship between knowledge sharing and business performance. The population of this research were Cafes and Restaurants in Payakumbuh City with a sample of 110 owners or managers. Data were collected through a questionnaire. Partial least squares structural equation modeling method (PLS-SEM) with SmartPLS 4 was used to analyze the data. The results of this study confirm that knowledge sharing has a positive effect on innovation. Knowledge sharing and innovation have a positive effect on business performance. The study also found a mediating effect of innovation on the relationship between knowledge sharing and business performance. The findings of this study state that knowledge sharing plays a role in improving the performance of cafes and restaurants either directly or through intermediary innovation.